Effect of Thrombin on Human Amnion Mesenchymal Cells, Mouse Fetal Membranes, and Preterm Birth - Mogami, Haruta (American Society for Biochemistry and Molecular Biology, 2014)
Here, we investigated the effects of thrombin on matrix metalloproteinases (MMPs) and prostaglandin (PG) synthesis in fetal membranes. Thrombin activity was increased in human amnion from preterm deliveries. Treatment of mesenchymal, but not epithelial, cells with thrombin resulted in increased MMP-1 and MMP-9 mRNA and enzymatic activity. Thrombin also increased COX2 mRNA and PGE(2) in these cells. Protease-activated receptor-1 (PAR-1) was localized to amnion mesenchymal and decidual cells. PAR-1-specific inhibitors and activating peptides indicated that thrombin-induced up-regulation of MMP-9 was mediated via PAR-1. In contrast, thrombin-induced up-regulation of MMP-1 and COX-2 was mediated through Toll-like receptor-4, possibly through thrombin-induced release of soluble fetal fibronectin. In vivo, thrombin-injected pregnant mice delivered preterm. Mmp8, Mmp9, and Mmp13, and PGE(2) content was increased significantly in fetal membranes from thrombin-injected animals. These results indicate that thrombin acts through multiple mechanisms to activate MMPs and PGE2 synthesis in amnion.